Understanding the Trends of Digital Literacy Among Islamic Students (Positive Internet Analysis Study) - Nazaruddin Musa; Norsiah Abdul Hamid; Mohd Sobhi Ishak (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
This study aimed to seek an in-depth understanding of digital trends among Islamic university students to use their literacy well and balanced on the positive internet. We believe that students' success using the facilities of digital technology is closely related to their proficiency in ICT. In order to understand easily, we chose the research method of research on the data findings that have been published in several journals that we can access with the Google Scholar data search engine published from 2010 to 2021. We involve analytical studies under the phenomenological approach to finding valid and reliable data. In the data review process, for example, we analyze data, evaluate, and critically interpret before drawing conclusions that answer the questions of this study. So one of the findings is that students can access lecture material using digital media skills to understand digital literacy. Their digital literacy is present positively and wisely because they have received training and use digital technology in a balanced way to make digital media an additional source of reference for proper and balanced lecture, game, and entertainment materials. These findings should be helpful in the development of future studies.